Neonatal adaptive behavioral assessment in asphyxiated full-term newborn infants as measured by the Brazelton scale - Lily Rundjan; Hardiono D Pusponegoro; Alan R Tumbelaka (Indonesian Pediatric Society, 2004)
Background Brazelton scale was designed to assess neonataladaptive behavior, a newborn infant’s ability to interact with envi-ronmental stimuli. It can be used as a screening tool to detect aninfant’s deviant behavior.Objective To assess the adaptive behavior of asphyxiated full-termnewborn infants compared to that of non-asphyxiated newborns.Methods A cross sectional analytic study was conducted from March2003 until March 2004. Subjects were allocated into two groups(non asphyxiated and asphyxiated infants) and enrolled consecu-tively. The evaluation was done twice, at the age of 3-7 days and 1month. A p value of <0.05 was considered statistically significant.Results Forty eight newborn infants in each group were compared.There were no characteristic differences between the groups. Atthe first evaluation, non asphyxiated infants scored better on mo-tor (p=0.015), reflex (p=0.000), habituation (p=0.022), and social-interaction (p=0.020) than asphyxiated infants did. At the age of 1month, motor (p<0.0001), reflex (p<0.0001), habituation(p<0.0001), state organization (p<0.0001), and social-interaction(p=0.045) were also better in non-asphyxiated infants.Conclusion Assesment by the Brazelton scale showed that theadaptive behavior of full-term asphyxiated newborn infants wasdifferent from that of non-asphyxiated infants